Hydroxyapatite Deposition Disease as Cause of Atraumatic Shoulder Pain: A Case Report - Hong Diem Truong; Andrew Gonedes; Jason Haidar; Kevin Wilson; Michael Remaly; Eric Boccio (Clinical Practice and Cases in Emergency Medicine)
Introduction: Hydroxyapatite deposition disease (HADD) is caused by the presence of hydroxyapatite crystals in periarticular spaces oftentimes leading to inflammation, pain, and decreased range of motion. Case Report: A 40-year-old right hand dominant female presented with three days of atraumatic right shoulder pain. Radiographs of the right shoulder were negative. Computed tomography revealed a hydroxyapatite deposit adjacent to the acromioclavicular joint. The patient was managed with nonsteroidal anti-inflammatory drugs and a referral to orthopedic surgery. Conclusion: Many instances of HADD will not be diagnosed on plain radiographs, and heightened awareness will provide confidence when ordering confirmatory imaging. Management is typically conservative, however, referral to orthopedic surgery is recommended to ensure improvement and to assess the need for more invasive procedures.